Delegado do DOPS x pastor evangélico repressão política, ditadura militar e deslocamento de memória em Cláudio Guerra (1964-1985) - Ferreira, Vinicius de Paula (2022)
The period between 1964 and 1985 is marked by the Brazilian Military Dictatorship. Through torture, repression, censorship, and other arbitrariness, the military persecuted, killed, and disappeared with thousands of people throughout its 21 years of power. Through the discourse of “eliminating the subversive” or the “enemy of the government”, the Dictatorship sought to silence all those who opposed the current “order”. In 1985, after the military left power, historiography began a series of discussions about the memory of the period, raising questions via testimonies, documents, and denunciations. In the last decade, the former delegate of the Department of Political and Social Order of the State of Espírito Santo (DOPS-ES), Cláudio Antônio Guerra, confessed to his crimes in the book Memories of a dirty war (2012). In 2014, he was referred to testify at the National Truth Commission (CNV). On that occasion, he again confessed to crimes and actions that he supposedly committed during the dictatorship. In 2018, the film/documentary Pastor Cláudio was produced, and once again, the confessed former repressor mentions his practices and his involvement with the military. By claiming to be immersed in a religious experience, Cláudio Guerra seeks to witness his crimes to show the possibility of finding “light” and “redemption”. Given the above, this Dissertation argues that through memory displacement, Cláudio Guerra seeks to assume his crimes until 1979, taking refuge in the Amnesty Law (1979). It is observed that after this time frame, the former delegate has denied committing practices typified as a criminal misdemeanor, crime of command, and smuggling. Finally, it is highlighted that through a liturgical effect in the speech, marked by redemption and repentance of sins, the character naturalizes and normalizes the violence he practiced. The documents mentioned above were used in this Dissertation as primary sources of research, using the methodology of document analysis.